Influence of intracervical and intravaginal seminal plasma on the endometrium in assisted reproduction: a double‐blind, placebo‐controlled, randomized study. (8th January 2015) - Mayer, R. B.; Ebner, T.; Yaman, C.; Hartl, J.; Sir, A.; Krain, V.; Oppelt, P.; Shebl, O.
ABSTRACT Objective To investigate the effect of intracervical and intravaginal application of seminal plasma on the endometrium, as assessed by endometrial/subendometrial vascularization and endometrial volume between the day of oocyte retrieval and the day of embryo transfer in an in‐vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycle. Methods This was a double‐blind, placebo‐controlled, randomized study including patients undergoing a first or second IVF/ICSI cycle. Homologous seminal plasma or placebo (sodium chloride) was injected into the cervix and posterior vaginal fornix just after follicle aspiration. Three‐dimensional power Doppler examination was performed 30 min before oocyte retrieval and 30 min before embryo transfer. Main outcome measures were changes in vascularization flow index (VFI), flow index (FI) and vascularization index (VI) of the endometrium/subendometrium using VOCAL™ (Virtual Organ Computer‐aided AnaLysis) and endometrial volume. Results One hundred patients agreed to participate in the study. Twenty‐three patients were excluded, mainly as a result of canceled embryo transfer. Data were analyzed from 40 patients receiving seminal plasma and 37 receiving placebo. No significant differences between the two groups were seen in VFI, FI or VI of the endometrium or subendometrium or in endometrial volume on the day of oocyte pick‐up and on the day of embryo transfer. Conclusion Neither endometrial/subendometrial vascularization parameters nor endometrial volume seem to be affected by the application of seminal plasma in patients undergoing their first or second IVF/ICSI cycle. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.